Monday
March 27, 2017

Post a New Question

Posted by on .

can someone explain step by step to solve system equations and example ill show here 3x+4y=-2 x=-2y

  • math - ,

    the simplest way for this example is to use substitution.
    sub x = -2y into 3x+4y = -2
    3(-2y) + 4y = -2
    -6x + 4y + -2
    -2y = -2
    y = 1
    then since x = -2y
    x = -2(1) = -2

  • math - ,

    so u simplify them and divide and basically is the answer.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question